Noninvasive assessment of patency of internal ureteral stent: Role of colour Doppler ultrasound - Lojanapiwat B. (2014)
OBJECTIVE: To compare colour Doppler ultrasonography (CDU) and retrograde cystography in the assessment of the patency of internal ureteral stents. PATIENTS AND METHODS: Thirty-two patients with 33 internal ureteral stents were evaluated for patency of the internal ureteral stent using both CDU and retrograde cystography. Real-time ultrasonography and CDU were performed before retrograde cystography. Stent patency was defined as seeing flow from the distal end of the stent in the urinary bladder or iodinated contrast in the renal pelvis. The two investigators had no prior knowledge of the other's results. After completion of both investigations, stent patency was proved by direct inspection of the stent after removal. RESULTS: Both investigations showed the same result in 27 of the 33 stents. Stent patency was found if either investigation was positive. The accuracies of retrograde cystography, CDU and both were 73%, 79% and 85%, respectively. CONCLUSIONS: CDU is a noninvasive method with high accuracy. Detection of flow at the distal end of the stent is helpful, but absence of flow may or may not indicate an obstructed stent and further investigation should be performed.